Fathers' childcare: The difference between participation and amount of time - Nora Reich (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
The main research question of this article is whether and how predictors of fathers' participation in childcare, defined as zero versus more than zero minutes of childcare, differ from predictors of participating fathers' amount of time on childcare, measured as minutes on the survey day. The sample is drawn from the Multinational Time Use Study (MTUS) and covers surveys from ten industrialised countries from 1987 to 2005. Results show that there are remarkable differences between factors influencing participation in childcare and factors associated with participating fathers' time spent with children. For example, the educational level has a strong impact on fathers' participation, but not on the amount of time spent on childcare. In contrast, work hours and whether data refer to a weekday or a weekend day hardly affect participation, but strongly affect fathers' time for childcare. There are also noticeable differences between the countries and between different points in time regarding factors influencing childcare participation and time. Results call for caution regarding findings from existing studies not distinguishing participation from participating fathers' childcare minutes.
Keywords: D13; J13; 330; childcare; fatherhood; time use; selection; Väter; Kinderbetreuung; Zeitverwendung; Schätzung; Westeuropa; Kanada